Dumezil between the east and west. Formulaic use of attributes white and heroic in South Slav oral epic poetry - Detelić, Mirjana (Zeitschrift für Balkanologie, 2011)
This article discusses the unexpected distribution of the attributes white and heroic in South Slavic (actually Serbo-Croatian) decasyllabic epic poetry, especially of the epic formula white town (general type: noun + attribute). Thе presented analysis is based equally on George Dumezil’s theory about tripartite structure of the ancient Indo-European society (Dumezil 1958; 1997) and on the theory of the pre-Indo-European origin of the Slavic decasyllabic verse by the Russian scholar Mikhail Gasparov (Gasparov 1989). Combined, they might explain why the toponomastic formula “white town” (Dumezil; Sauzeau 2005), while present in the traditions of all Slavic peoples, as an epic device of regular appearance and high frequency can be traced only in Serbo-Croatian decasyllabic (Gasparov; Jakobson 1966) epic poetry. Today it is completely lost in its territory of origin (East and West Slavs, even Bulgarians – Petkanova 1983; Propp 1958), but it remains preserved at the periphery of its former kernel. In terms of space, this periphery is the borderline between South Slavic people and other ethnolinguistic groups (Greeks, Hungarians, Germans, Italians). This also means that in Serbo-Croatian oral tradition it has remained unchanged from the times before the Great Movement of peoples, because in issues of folklore the periphery is always much more conservative and oppressive to changes than the centre. However, to stay the same for so long, a pattern, formula or another device had to be covered by taboo and be forbidden to change, which means it must have been sacral. Only in that context the piles of bones of sacrificial animals, as mentioned in medieval descriptions of some West Slavic sacred places for worship and adoration of gods (like Rhetra – Mecklenburg in present Germany, in Nestor Chronicles), correspond perfectly to the many mythic and fairy towns built from human and horse bones in South Slavic oral epic poetry. Nothing less important and holy could stand the trial of so long a passage of time. Furthermore, this ancient formula came down to us wrapped in an equally ancient kind of verse, which Gasparov successfully traced to its pra-Indo-European roots from whence it was freely distributed throughout the Slavic world. Othervise, the here-discussed epic image of town could have hardly remained unchanged in two culturally, religiously, socially, legislatively, and in every other way different world-views of Christians and Moslems with South-Slavic origin, which from the beginning of 16th or 17th century was – and still is – the actual situation regarding epic singers in the Balkans. They could not share their relatively recent history for easily understandable reasons, but this attribute + noun formula was older than history as they saw it, older even than singing itself.